Alternating Donor–Acceptor π‐Conjugated Macrocycle Exhibiting Efficient Thermally Activated Delayed Fluorescence and Spontaneous Horizontal Molecular Orientation. Issue 7 (21st May 2021) - Shikita, So; Watanabe, Go; Kanouchi, Dai; Saito, Junya; Yasuda, Takuma
Abstract : A versatile design of thermally activated delayed fluorescence (TADF) π‐conjugated macrocycles incorporating electron‐donor (D) and acceptor (A) units into a cyclo‐meta‐phenylene motif with an alternating pattern is presented. The new π‐conjugated macrocycle, which combines three 5‐( N ‐carbazolyl)‐phenylen‐1, 3‐diyl as D units and three 6‐phenyl‐1, 3, 5‐triazin‐2, 4‐diyl as A units, possesses a small singlet–triplet energy gap and hence can emit efficient green TADF both in solution and doped thin films. Comparative experimental and computational investigations of the electronic and photophysical properties of the macrocycle with its analogous noncyclic compound reveal key advantages of the cyclic molecular configuration for actual emitters. Organic light‐emitting diodes incorporating the TADF π‐conjugated macrocycle as an emitter demonstrate high external electroluminescence quantum efficiencies of up to 15.7%, outperforming the devices based on the noncyclic emitter. Herein, the importance of geometric design for producing novel organic emitters with fascinating optoelectronic and morphological characteristics is highlighted. Abstract : A novel thermally activated delayed fluorescence (TADF) π‐conjugated macrocycle combining three electron‐donating 5‐( N ‐carbazolyl)‐phenylen‐1, 3‐diyl units and three electron‐accepting 6‐phenyl‐1, 3, 5‐triazin‐2, 4‐diyl units is developed, and its structural, electronic, photophysical, and electroluminescence properties are systematically investigated and compared with those of the noncyclic trimeric counterpart.